Blue light-emitting diode: a new adjuvant approach to conventional treatment of recurrent vulvovaginal candidiasis - Isadora Bastiani Biondo; Rodrigo Rossi Balbinotti; Fernanda Santos Grossi; Eduardo Vettorazzi-Stuczynski; Janete Vettorazzi (Photodiagnosis and Photodynamic Therapy)
Recurrent vulvovaginal candidiasis (RVVC) presents challenges due to the adverse effects and resistance associated with prolonged antifungal therapy, highlighting the need for alternative treatments. This single-blind randomized trial evaluated intravaginal phototherapy with a 415 ± 13.7 nm blue LED as an adjunct to standard RVVC therapy. Participants were randomized to a control group (no light for 35 min) or experimental groups (light for 30 or 40 min) over three weekly sessions at 7 ± 3-day intervals. Clinical evaluations, microbiological analyses, and questionnaire assessments were conducted during the sessions and at 30 and 180 days, with symptom monitoring at 60, 90, 120, and 150 days. Thirteen women (mean age 28.92 years) were randomized into three groups: 30-minute (n = 5), 40-minute (n = 4), and control (n = 4). At 30 days, 61.5 % of participants showed a reduction of 50 % or more in the semiquantitative scores of signs and symptoms, rising to 76.9 % at 180 days, with the greatest improvements in the 30-minute and control groups. Significant symptom reduction was observed in the control group (p < 0.001). At 180 days, 53.8 % of participants had negative Candida cultures, predominantly in the 30-minute group. The therapy was well-tolerated, with high satisfaction scores in the control (5.00 ± 0.20) and 30-minute groups (4.20 ± 0.33). Phototherapy with a 415 ± 13.7 nm blue LED for 30 min demonstrated therapeutic potential as an adjunctive treatment for RVVC. Further studies with longer follow-up periods and larger sample sizes are needed to validate these findings and strengthen clinical evidence.